2002
DOI: 10.1007/s00784-002-0168-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of buccal epithelial cells by alkaline comet assay (single cell gel electrophoresis technique) in cytogenetic evaluation of chlorhexidine

Abstract: During the last few years, there has been increasing interest in buccal epithelial cells for cytogenetic evaluation of different materials. In the present study, the use of these cells and peripheral lymphocytes for cytogenetic evaluation of chlorhexidine digluconate (CHX) with comet assay (single cell gel electrophoresis, or SCGE) is reported. This technique detects DNA strand breaks in individual cells in alkaline conditions. Thirteen volunteers were requested to rinse their mouths with 0.12% CHX solution fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 30 publications
2
43
0
1
Order By: Relevance
“…Our results have demonstrated that Periogard® containing chlorhexidine at 0.12% was able to induce cytogenetic damage as depicted by the increase of micronucleus frequency after continuous exposure. By comparison, a level of DNA damage in peripheral blood lymphocytes and buccal mucosa cells was evidenced in individuals exposed to chlorhexidine digluconate at 0.12% for 2 weeks by single-cell gel (comet) assay [19]. In particular, a previous study conducted by our research groups has consistently demonstrated that Periogard® induced genetic damage in peripheral lymphocytes and buccal mucosa cells of rats [28].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results have demonstrated that Periogard® containing chlorhexidine at 0.12% was able to induce cytogenetic damage as depicted by the increase of micronucleus frequency after continuous exposure. By comparison, a level of DNA damage in peripheral blood lymphocytes and buccal mucosa cells was evidenced in individuals exposed to chlorhexidine digluconate at 0.12% for 2 weeks by single-cell gel (comet) assay [19]. In particular, a previous study conducted by our research groups has consistently demonstrated that Periogard® induced genetic damage in peripheral lymphocytes and buccal mucosa cells of rats [28].…”
Section: Discussionmentioning
confidence: 96%
“…Test materials, manufacturers, and ingredients are listed in Table 1. All volunteers were requested to rinse their mouths with 15 ml of mouthrinse twice a day for 2 weeks as described elsewhere [19]. The rinsing procedures took approximately 30 s each time.…”
Section: Micronucleus Test In Buccal Mucosa Cellsmentioning
confidence: 99%
“…In this context, aside from lymphocytes, the assay has been carried out using whole blood [ 31 ], buccal epithelial cells [ 32 ], tear duct epithelial cells [ 33 ], and sperm [ 34 ]. The selection of the cell population to use must be based on exposure conditions, persistence of DNA damage, and rates of cell turnover.…”
Section: Sample Type Collection and Processingmentioning
confidence: 99%
“…Although SCGE studies have also been conducted on BM cells [Rojas et al, 1996;Valverde et al, 1997;Eren et al, 2002;Dhillon et al, 2004], low cell viability, saprophyte bacterial contamination, and their specialized cellular membranes, which make cell lysis difficult, contribute to making BM cells a more complicated cell to analyze compared with leukocytes. In this study, we evaluated the properties of BM cells in the SCGE assay and developed methodology for performing adequate cell lysis and enriching for viable cells in exfoliated BM cell samples.…”
Section: Introductionmentioning
confidence: 99%